Cibercultura e ciberespaço: as relações sociais nos jogos online como extensão do homem social e político - Nunes, Daniel Salgado Galvão (2016)
The relationships and social interactions that occurs through Information and Communication Technologies can be considered reals? Is there a politic, ethic or aesthetic model that need to be followed in this context, and if it exists it is similar to real world models? The users of Technologies, and mainly online gamers, are affected by the act of playing electronic games? The development of this research and dissertation was initially motivated by these investigations, and posteriorly became more complex. Questioning the way of think technology use and how to think this use were the start point, but just these questions are insufficient to comprehend the virtualization, the virtual and all your fecundity. From there, think the influences of playing games, mainly in our days, in man formation guided the core of this research.